Pengaruh Penguatan Literasi Melalui Program Bimbingan Belajar Terhadap Kesulitan Membaca Siswa Kelas 1 SDN Pakis V Surabaya - Suryani, Suryani; Noerhartati, Endang; Roosyanti, Anna (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to determine the effect of strengthening literacy through tutoring programs on reading difficulties in first-grade students at SDN Pakis V Surabaya. This research uses a qualitative approach with a descriptive method. Data collection techniques were carried out through observation, interviews, documentation, and reading ability tests (pretest and posttest). The subjects in this study were 10 first-grade students who experienced reading difficulties, a class teacher, and the students' parents. The results of the study indicate that the tutoring program significantly improved students' reading skills. After implementing the program over eight meetings, there was an improvement in the ability to recognize letters, syllable formation, reading simple words and sentences, as well as comprehension of the reading content. This program has a positive impact on students' learning motivation and self-confidence. The success of this tutoring program is influenced by several important factors, namely: (1) active involvement of teachers in providing individual and group support, (2) the use of engaging teaching media that meets the developmental needs of students such as letter cards, pictures, and simple reading books, (3) parental involvement in supporting the learning process at home, (4) enjoyable learning approaches that are suitable for early childhood characteristics, and (5) the consistency and intensity of the structured implementation of the tutoring program.